Atmospheric eddies mediate lapse rate feedback and arctic amplification - Feldl N.; Anderson B. T.; Bordoni S. (Journal of Climate, 2017)
Projections of amplified climate change in the Arctic are attributed to positive feedbacks associated with the retreat of sea ice and changes in the lapse rate of the polar atmosphere. Here, a set of idealized aquaplanet experiments are performed to understand the coupling between high-latitude feedbacks, polar amplification, and the large-scale atmospheric circulation. Results are compared to CMIP5. Simulated climate responses are characterized by a wide range of polar amplification (from none to nearly 15-K warming, relative to the low latitudes) under CO2 quadrupling. Notably, the high-latitude lapse rate feedback varies in sign among the experiments. The aquaplanet simulation with the greatest polar amplification, representing a transition from perennial to ice-free conditions, exhibits a marked decrease in dry static energy flux by transient eddies. Partly compensating for the reduced poleward energy flux is a contraction of the Ferrel cell and an increase in latent energy flux. Enhanced eddy energy flux is consistent with the upper-tropospheric warming that occurs in all experiments and provides a remote influence on the polar lapse rate feedback. The main conclusions are that (i) given a large, localized change in meridional surface temperature gradient, the midlatitude circulation exhibits strong compensation between changes in dry and latent energy fluxes, and (ii) atmospheric eddies mediate the nonlinear interaction between surface albedo and lapse rate feedbacks, rendering the high-latitude lapse rate feedback less positive than it would be otherwise. Consequently, the variability of the circulation response, and particularly the partitioning of energy fluxes, offers insights into understanding the magnitude of polar amplification.